Direct evidence on income comparisons and their welfare effects - Claudia Senik (Institute for the Study of Labor (IZA), 2007)
This paper provides unheard direct evidence that comparisons exert a significant effect on subjective well-being. It also evaluates the relative importance of different types of benchmarks. Dynamic comparisons outweigh static ones. Internal benchmarks are more important than external reference groups. Local comparisons (to parents, former colleagues or school classmates) are more powerful than general comparisons such as my rank in the social ladder. The most important impact comes from the deterioration of my living standard and from under-performing my former schoolmates or colleagues. A possible interpretation is that comparisons benchmarks are all the more significant as they are interpreted in terms of seized or lost opportunities.
Keywords: C25; 330; Subjective well-being; income comparisons; income mobility; internal and external benchmarks; transition; Lebenszufriedenheit; Einkommensverteilung; Interpersoneller Nutzenvergleich; Übergangswirtschaft; Osteuropa